Integração curricular em programas de formação de professores: análise do desenvolvimento curricular do Programa PEC Municípios - Ferreira, Marisa Vasconcelos (2008)
This research draws on the idea that the hegemonic curricular organization in the context of modern school constitutes and reedits the fragmentations and segmentations that characterize children´s, youngsters and adults teaching-learning process, which includes the process of teacher education. Having these fragmentations as a counterpoint, we describe the assumptions and some conditions that frame our perspective towards teacher education. Furthermore we propose an articulation of the assumptions concerning teacher education with the perspective of curriculum integration, which materializes itself in different and articulated dimensions such as the integration of experiences, social integration, knowledge integration and integration itself as a curricular conception, according to James Beane (1997). Along that line, through the analysis of the curriculum development of a special teacher education program, PEC Municípios (Undergraduate Teacher Education Program Municipalities), we attempt to identify curriculum integration elements, trying to figure out how the different dimensions of this integration were concretely dealt within the program. PEC Municípios was held during the years 2003 and 2004, as a partnership that included the State of São Paulo Department of Education, the Municipal Departments of Education of 41 cities in the State of São Paulo and two universities (USP The University of São Paulo and PUC-SP The Pontifical Catholic University of São Paulo). This program certified, with a college degree diploma, 4,500 preschool and elementary school (from 1st to 4th grades) teachers who worked in municipal schools. As a whole, we identified the presence of important teacher education elements that deal with aspects of curriculum integration such as the interinstitutional character of the Program, the permanent presence of teacher educators within the Program, the articulation of various interactive media and of various types of activities which, on their side, integrate different teachers knowledge, as stated by Tardif (2002), among others. On the other hand, we observed the absence, or even the weakness of some elements such as the lack of participation of the educators and of the student teachers in the process of curriculum design, the emphasis on the development of an individual autonomy, which reduces the conditions for school team work a requirement for the articulation and development of integrated teaching in and of the school community. Thus, we can identify advances that may become recommendations for other experiences concerning teacher education, including regular undergraduate Teacher Education, and we can also identify challenges for the design of an integrated teacher education curriculum and for educational policies guided by integration and continuity